ANALISIS BUDAYA ORGANISASI PADA PARIWISATA KABUPATEN BIAK NUMFOR - Aprillia Cenyo Mofu; Fatmawada; Dahlan Lan (Mimbar Administrasi Mandiri, 2023)
Analysis of Organizational Culture at the Biak Numfor Regency Tourism Oflce. This study aims to determine the characteristics of organizational culture on the socialization process and communication factors of organizational culture at the Biak Numfor Regency Tourism Oflce. This research is descriptive quantitative with a population of all employees at the Biak Numfor Regency Tourism Oflce totaling 59 people. Data analysis techniques are interactive models and qualitative analysis with descriptive data collection processing data, analyzing data, describing data, and making decisions. The results showed that the characteristics of organizational culture at the Biak Numfor Regency Tourism Oflce were running well, it was just lack of internal communication that hindered the work motivation of employees at the Biak Numfor Regency Tourism Oflce. The process of socialization of Organizational Culture at the Biak Numfor Regency Tourism Oflce is going well, seen from health protocols, tourist boards, books containing history, destination descriptions and destination pictures. For the process of organizational culture communication factors at the Biak Numfor Regency Oflce, it is still less eﬀective, seen from the obstacles to communicating between people who make organizational goals less eﬀective, so that there is a signiﬁcant inﬂuence between the characteristics of Organizational Culture with the socialization process and communication factors of Organizational Culture at the Biak Numfor Regency Tourism Oflce.